Quantum rate dynamics and charge screening at the nanoscale level - Pinzón Nieto, Edgar Fabian [UNESP]; Alarcón, Erika Viviana Godoy [UNESP]; Sánchez, Yuliana Pérez [UNESP]; Bueno, Paulo Roberto [UNESP] (Royal Society of Chemistry (RSC), 2022)
It has been demonstrated that quantum-rate electrodynamics originate from charged quantum states within redox moieties coupled to electrodes. In this study, we demonstrate that this phenomenon is not restricted to redox reactions, and that it is applicable to certain charge screening conditions that depend on electron-ion pairing phenomena. Quantum-rate electrodynamics governs the dynamics of charged inorganic semiconductor states at the nanoscale level. This makes quantum-rate electrodynamics a crucial factor in the design of tailored interfaces within quantum charge transport, determining the efficiency of these interfaces. The applications of quantum-rate electrodynamics range from sensors to supercapacitors.